Automatic front light switching system / Muhamad Yusof Mohd Noor, Mohammad Azim Sahid Sani and Muhammad Afifi Zainal - Mohd Noor, Muhamad Yusof; Sahid Sani, Mohammad Azim; Zainal, Muhammad Afifi (2013)
Automatic front light switching system is a technology to reduces the amount of accidents happen, such as prevent from who are forget to switching the front light from high beam to low beam and vice versa. Besides that, it is to increased safety among traffic road users that are provide clear visibility under all circumstances and immediate response because the light automatic switching to high beam as the vehicle through the dark road and vice versa. This project is using integrated circuit type LM741, photodiode and AND gate. Firstly, it will detect the condition of surrounding whether it dark or not, if it’s dark the lamp automatically will change to high beam and vice versa. It also will detect the presence of object in front of car. If the sensor detects the object it will turn to low beam and vice versa. The automatic front light switching system make the journey be more comfortable as they do not have to switch the light when it comes to certain states.